Factors predicting quality of work life among nurses in tertiary‐level hospitals, Bangladesh. (3rd November 2017) - Akter, N.; Akkadechanunt, T.; Chontawan, R.; Klunklin, A.
Abstract : Aim: This study examined the level of quality of work life and predictability of years of education, monthly income, years of experience, job stress, organizational commitment and work environment on quality of work life among nurses in tertiary‐level hospitals in the People's Republic of Bangladesh. Background: There is an acute shortage of nurses worldwide including Bangladesh. Quality of work life is important for quality of patient care and nurse retention. Nurses in Bangladesh are fighting to provide quality care for emerging health problems for the achievement of sustainable development goals. Methods: We collected data from 288 randomly selected registered nurses, from six tertiary‐level hospitals. All nurses were requested to fill questionnaire consisted of Demographic Data Sheet, Quality of Nursing Work Life Survey, Expanded Nursing Stress Scale, Questionnaire of Organizational Commitment and Practice Environment Scale of the Nursing Work Index. Data were analysed by descriptive statistics and multiple regression. Results: The quality of work life as perceived by nurses in Bangladesh was at moderate level. Monthly income was found as the best predictor followed by work environment, organizational commitment and job stress. Discussion: A higher monthly income helps nurses to fulfil their personal needs; positive work environment helps to provide quality care to the patients. Limitation: Quality of work life and predictors measured by self‐report only may not reflect the original picture of the quality of work life among nurses. Conclusion and policy implications: Findings provide information for nursing and health policymakers to develop policies to improve quality of work life among nurses that can contribute to quality of nursing care. This includes the working environment, commitment to the organization and measures to reduce job stress.